2012
DOI: 10.1039/c2tx20023f
|View full text |Cite
|
Sign up to set email alerts
|

Detection of genotoxic and non-genotoxic renal carcinogens in vitro in NRK-52E cells using a transcriptomics approach

Abstract: There is a need to develop quick, cheap, sensitive and specific methods to detect the carcinogenic potential of chemicals. Currently there 10 is no in vitro model system for reliable detection of non-genotoxic carcinogens (NGTX) and current tests for detection of genotoxic carcinogens (GTX) can have low specificity. A transcriptomics approach holds promise and a few studies have utilised this technique. However, the majority of these studies have examined liver carcinogens with little work on renal carcinogens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…The authors considered this as evidence of a non-genotoxic MoA. Bloch et al (2012) attempted to distinguish between genotoxic and non-genotoxic renal carcinogens based on their profile of alteration of gene expression in NRK-52E cells, using OTA to represent the non-genotoxic class of carcinogen. However, several pathways were common to both genotoxic and non-genotoxic categories making distinction not possible.…”
Section: Mode Of Action In Carcinogenesismentioning
confidence: 99%
“…The authors considered this as evidence of a non-genotoxic MoA. Bloch et al (2012) attempted to distinguish between genotoxic and non-genotoxic renal carcinogens based on their profile of alteration of gene expression in NRK-52E cells, using OTA to represent the non-genotoxic class of carcinogen. However, several pathways were common to both genotoxic and non-genotoxic categories making distinction not possible.…”
Section: Mode Of Action In Carcinogenesismentioning
confidence: 99%
“…5 We found that MON at 250 μM (IC 10 at 72 h in rat renal cells) did not induce micronucleus formation. 11 However, studies in Chinese hamster ovary (CHO) cells noted a small increase in chromosome aberrations, which were markedly increased in the presence of Aroclorinduced rat liver S9, indicating MON-induced chromosome aberrations, albeit at a concentration of 1.3 mg ml −1 (6.55 mM). 5 MON also caused transformation in Syrian hamster embryo cells in the absence of metabolic acti-vation.…”
Section: Introductionmentioning
confidence: 99%